2016
DOI: 10.1007/s12603-015-0602-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of objective physical activity, muscle strength, and depression among community-dwelling older women living in sloped versus non-sloped environments

Abstract: Since dwelling on sloped ground was associated with negative (lower physical activity levels, lower grip strength, and more depression) outcomes, a comprehensive geriatric assessment, related to all aspects of older women, is recommended. Planning of home exercise programs for the elderly should take such environmental factors into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…The association between depressive symptoms with lack of sleep and lower back pain as individual factors was also shown. Our findings are consistent with a previous study [ 21 ]; Tanaka et al reported that older women living in sloped areas had higher depression levels than individuals residing in non-sloped areas in urban Japan [ 21 ]. In this previous study [ 21 ], sloped and non-sloped areas were defined as more or less than five degrees, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The association between depressive symptoms with lack of sleep and lower back pain as individual factors was also shown. Our findings are consistent with a previous study [ 21 ]; Tanaka et al reported that older women living in sloped areas had higher depression levels than individuals residing in non-sloped areas in urban Japan [ 21 ]. In this previous study [ 21 ], sloped and non-sloped areas were defined as more or less than five degrees, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, it is possible that there exists a relationship between living in a hilly rural environment and depressive symptoms. Although a previous study conducted in an urban area found that a hilly environment was positively associated with depressive symptoms in older women [ 21 ], no study has been conducted in a rural setting. Therefore, in the present study, we investigated whether land slopes were associated with depressive symptoms in older Japanese adults living in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed a correlation between slope and the level of walkability [56,57]. In particular, the slope was more sensitive to the walking behavior for the elderly [58][59][60]. In this study, the slope is included as an environmental variable and is defined as the mean slope within a 400 m network buffer from the centroid of an apartment complex.…”
Section: • Slopementioning
confidence: 99%
“…Only 10 studies (14%) had 300 or fewer participants (considered to be a small sample size), whereas 37% had sample sizes >2,500, allowing detection of very small effects. Nine studies examined participants from minority race/ethnic groups (Okwumabua et al, 1997;Curyto et al, 1998;Ostir et al, 2003;Brown et al, 2009;Gerst et al, 2011;Roh et al, 2011;Kwag et al, 2012;Kim et al, 2013;Hernandez et al, 2015) and three were gender specific (Wilcox et al, 2003;Saarloos et al, 2011;Tanaka et al, 2016). A total of 96% of the scales used to determine possible depression and depressive symptoms were known to be validated.…”
Section: Study Design Bmentioning
confidence: 99%